Extreme UV sensitivity of native Metarhizium spp. as potential biocontrol agent for False Codling Moth (Thaumatotibia leucotreta Meyrick) on chili pepper in Ghana - Nyahe, Patricia Akua Sitsofe; Eziah, Vincent Yao; Al-Ani, Laith Khalil Tawfeeq; Akumyoungta, Monica; Coombes, Candice Anne; Rangel, Drauzio Eduardo Naretto; Alder-Rangel, Alene; Sukmawati, Dalia; Aidoo, Owusu Fordjour; Acheampong, Mavis Agyeiwaa (Frontiers in fungal biology, 2025)
Chili pepper exports from Ghana are subject to stringent chemical residue regulations in key export destinations. Consequently, microbial biopesticides are urgently needed to complement current nonchemical control options for key pests of chili pepper, particularly the phytosanitary insect, False Codling Moth (FCM). Thus, the search for native entomopathogenic fungi in Ghanaian farms was initiated in 2023. Seven Metarhizium isolates (UGSUHCI, UGJKCS9, UGJKCS10, UGAFMF8, UGAFM F12, UGNAKC1 and UGKAP1), obtained from agricultural soils in Ghana, showed high virulence against the soil-dwelling stages of FCM under laboratory conditions. To facilitate the selection of these virulent isolates for development into a mycoinsecticide for FCM, the UV sensitivity and virulence following UV exposure were investigated for all seven isolates in this study. All isolates exhibited extreme susceptibility to UV radiation in comparison to similar research. Exposure to simulated full-spectrum solar radiation at 0.6 W/m 2 for 30 min reduced relative conidial germination by 28–40% 48 h following exposure, while 60 min exposure killed all isolates. High insect mortalities were recorded for four isolates, regardless of UV radiation. The findings suggest that an effective UV-protectant formulation could be required for success in the field against fruit and foliar pests of chili pepper, including those of FCM.